2015
DOI: 10.5433/1679-0359.2015v36n6p3751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Musa spp. extract on eggs and larvae of gastrointestinal nematodes from infected sheep

Abstract: ResumoAs helmintoses figuram como um dos principais entraves para o desenvolvimento da caprinoovinocultura. Haemonchus contortus é a espécie que causa maior impacto nesta atividade pecuária. A resistência às drogas antiparasitárias e a procura por alimentos de origem animal livre de resíduos tem elevado a importância de tratamentos fitoterápicos. O objetivo desse trabalho foi desenvolver um extrato de Musa spp. e avaliar através de testes in vitro o efeito anti-helmíntico sobre ovos e larvas de nematódeos gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
5
0
3
Order By: Relevance
“…Extracts of the leaves and stem of Musa spp. showed inhibition of ovine nematodes (NEUWIRT et al, 2015). However, these authors used banana leaves and higher doses than those used in this study, i.e 160-180 mg mL -1 to evaluate the hatching test and 800-1000 mg mL -1 to evaluate the larval migration inhibition test.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Extracts of the leaves and stem of Musa spp. showed inhibition of ovine nematodes (NEUWIRT et al, 2015). However, these authors used banana leaves and higher doses than those used in this study, i.e 160-180 mg mL -1 to evaluate the hatching test and 800-1000 mg mL -1 to evaluate the larval migration inhibition test.…”
Section: Resultsmentioning
confidence: 91%
“…However, for ovines, it was not possible to observe the influence on larval hatchability and migration, at any of the concentrations evaluated in the present study. However, despite these results, continuation of the study for this species is justified, mainly by evaluating higher doses and performing complementary tests, as anthelmintic activity was verified in previous researches (MARIE-MAGDELEINE et al, 2014;NEUWIRT et al, 2015;NOGUEIRA et al, 2012). The bracts of the heart of Musa spp.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…They found a mean inhibition of 48.5%. Neuwirt et al (2015) reported a 100% inhibition in GIN eggs, with alcoholic extracts of Musa spp., using a 180 mg/mL concentration, a considerably higher quantity than that used in this study.…”
Section: Egg Hatching Testmentioning
confidence: 99%
“…Estudos realizados com o objetivo de controlar parasitos e reduzir os impactos da resistência, têm relacionado diversas plantas taniníferas com propriedades anti-helmínticas, dastacando-se a bananeira (Musa spp.) (Neuwirt et al, 2015;Nogueira et al, 2012). De acordo com Niezen et al (1995) a utilização de plantas ricas em taninos condensados pode ser indicada como alternativa no controle de verminose em ovinos, reduzindo o uso de produtos sintéticos, bem como os custos de produção.…”
Section: Introductionunclassified